Abdominal distension and lower extremity edema - Shaheen Andreas; Henry Chicaiza (Journal of the American College of Emergency Physicians Open)
Abstract Posterior urethral valves are a congenital malformation in males that results in the obstruction of urinary outflow from the proximal urethra. Presentation depends on severity of disease, with patients presenting antenatally with oligohydramnios and hydronephrosis, to postnatally with delayed or poor voiding, urinary tract infections, or renal anomalies on ultrasound. Our case illustrates an 11‐day‐old male who presented to the emergency department with poor feeding, vomiting, significant abdominal distension, and pitting edema of the lower extremities. The patient was found to have hypoglycemia, hyponatremia, hyperkalemia, and acute renal failure. Point of care ultrasound showed severe bilateral hydronephrosis with a significantly distended bladder that was compressing the inferior vena cava. Early recognition of the obstruction via ultrasound led to rapid decompression of the bladder using catheterization and immediate involvement of urology, nephrology, and neonatology consults in the pediatric emergency department.